Minimally invasive spine surgery strategy for congenital cervicothoracic scoliosis in children: Less blood loss and shortened segmental fusions/fewer pedical screws - Zhiguo, Zhou; Fan, Liu; Yuanxue, Lei; Xing, Wu; Si, Wang; Ruichen, Li (Frontiers in Surgery, 2023)
Objective: To explore the feasibility of minimally invasive spine surgery for congenital cervicothoracic scoliosis. Materials and methods: From April 2022 to August 2022 in the hospital, three patients with torticollis and/or shoulder imbalance due to a cervicothoracic hemivertebra were performed on by hemivertebra resection and short fusion of the adjacent vertebrae. Resection was operated by a posterior approach. The average age of three patients of surgery was 8 years 2 months and the mean follow-up period was 6 months. Radiographic assessments and cosmetic outcomes were documented on changes in measurements of segmental scoliosis, neck tilt, head shift, shoulder balance and sagittal profiles. Results: The mean operating-time of the procedure was 283 minutes and the instrumentation density was 1.5 pedicle screws per vertebra. The mean estimated blood loss was 257ml, which was 20% less than the data described in literatures. Mean segmental Cobb angle at the cervicothoracic deformity was 35.9° before surgery, 20.7° after surgery, and 16.3° at the latest follow-up, with a correction rate of 54.59%. Neck tilt decreased from 17.3° before surgery to 14.3° after surgery, and 11.7° at the latest follow-up, with a correction rate of 32.37%. T1 tilt improved from 16.5° before surgery to 12.9° after surgery, and 7.6° at the latest follow-up, with a correction rate of 53.94%. Clavicle angle improved from 4.8° before surgery to 3.1° after surgery, and 1.9° at the latest follow-up, with a correction rate of 60.42%. Head shift improved from 21.4 mm before surgery to 9.2 mm after surgery, and 12.3 mm at the latest follow-up, with a correction rate of 42.52%. The correction of torticollis and shoulder asymmetry was achieved in all cases. Conclusions: Minimally invasive spine surgery strategy may be an option for congenital cervicothoracic scoliosis. A good correction of cervicothoracic dissymmetry is achieved, accompanied with fewer pedicle screws and less blood loss. By deliberate operation in young kids, surgical intervention for severe compensatory curves can be prevented.